2016
DOI: 10.5539/ijbm.v11n6p194
|View full text |Cite
|
Sign up to set email alerts
|

Innovation & Performance Measurement: An Adapted Balanced Scorecard

Abstract: The aim of this paper is to offer an adaptation of the Balanced Scorecard (BSC) to improve performance measurement within research-intensive network. The paper employs the case study of the network Campania Bioscience to develop an innovation-oriented BSC to show the practical potential of this integrated theoretical approach to innovation, measurement, and control. The study develops specific key performance areas and indicators to enrich each of the four perspectives with the innovation elements (only implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Ability to introduce new products/services [80], [94], [12], [45], [95] Innovation, Learning and Growth Perspective (UR). [80], [94], [12], [95], [37] Source: The author, review, and classification of the data on indicators found in the papers in the references.…”
Section: Internal Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…Ability to introduce new products/services [80], [94], [12], [45], [95] Innovation, Learning and Growth Perspective (UR). [80], [94], [12], [95], [37] Source: The author, review, and classification of the data on indicators found in the papers in the references.…”
Section: Internal Businessmentioning
confidence: 99%
“…They also propose the introduction of new metrics, intending to adapt and apply them to different sectors. Better communication, more measurements, and more assessments contribute to better corporate governance [37].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous innovation objectives may be set, and performance measurement methods may build on the data provided by management control systems (see Spano et al, 2016;Tervala et al, 2017). However, it is the concept of innovation efficiency understood as "more innovation outputs with respect to the inputs" (Roth, 2015 p. 281) that seems to allow the comprehensive evaluation of innovation success (Arundel, Kemp, 2009).…”
Section: Decision-making Quality and Innovation Process Efficiencymentioning
confidence: 99%
“…From this perspective, appropriate managerial tools for innovation capacity and performances are vital to innovative organizations working in RD&I networks, mainly because they can ease information flows among the various actors involved (Spanò et al, 2016;Franco-Santos and Bourne, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To measure and evaluate the innovation capacity and performance at the organization level, the BSC approach can be considered a proper measurement and managerial framework, but only if there is a reasonable attempt to adapt the original framework. The required methodological adjustments refer mainly to the insertion of strategic innovation goals, key indicators, and metrics associated with them within each of the BSC perspectives (Gama et al, 2007;Spanò et al, 2016).…”
Section: Introductionmentioning
confidence: 99%